KEPEMIMPINAN PEREMPUAN DALAM ORGANISASI MUSLIMAT DAN AISYIAH DI KABUPATEN TULUNGAGUNG PERSPEKTIF LIVING QURAN - Fardan Mahmudatul Imamah; Amalia Rizky Firlana (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Women's leadership is still a controversial issue in religious' perspective, even though most women have received equal education and employment to men. The controversy emerges from different opinions about the interpretation of An-Nisa verse 34. This study discusses how women who are active in religious organizations define women's leadership based on the verse. There are two organizations as research subjects, namely Muslimat and Aisyiah in Tulungagung Regency. With the Living Quran approach, this research shows that women’s insight on women's leadership have diverse spectrum influenced by their religious understanding of the Quran as well as organizational policies and daily experiences. Muslimat provides greater tolerance for it, especially in the political and social fields. As for Aisyiah, despite accepting women's leadership as a today’s necessity, they still limit theirself to political leadership, especially as governmental head. However, both Muslimat and Aisyiah agreed that the An-Nisa verse 34 is a verse that explain the relationship between men and women in the household, so it could not be generalized to prohibit women's leadership in the public sphere.